BLOCK_PLASTER: high energy/environmental performance brick building envelope - Carbonaro, Corrado; Tedesco, Silvia; Fantucci, Stefano (TECHNE - Journal of Technology for Architecture and Environment, 2018)
Today, technological innovation in the construction field faces an important challenge: the identification of solutions that may not only allow to maximize energy saving in the use phase, but that may also reduce environmental impact throughout the entire life cycle of materials and components. The paper illustrates a research activity and experimentation – funded by the European Union – carried out in synergy by research centres and private companies. Its end purpose was the design, prototyping, and monitoring of an eco-friendly brick envelope named BLOCK_PLASTER. Alternative configurations to the system have been identified and technological-environmental performances in the different phases of the life cycle have been verified through a multidisciplinary and a multi-objective approach.